2015
DOI: 10.4103/2249-4863.152262
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and burden of psychiatric disorders in primary health care visits in Qatar: Too little time?

Abstract: Background:Psychiatric disorders including anxiety, depression, somatization, obsessive compulsive, and bipolar disorders are recognized as causing the biggest burden of disease worldwide.Aim:In this study, we aimed to assess the prevalence and burden of common mental disorders at Primary Health Care Centers (PHCC) using the World Health Organization Composite International Diagnostic Interview (WHO-CIDI) in the Qatari population, aged 18–65 who attended Primary Health Care (PHC) settings.Design:A prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 32 publications
2
32
0
1
Order By: Relevance
“…The point prevalence of PTSD diagnosis ascertained by diagnostic interviews (e.g., Structured Clinical Interview [SCID], Diagnostic Interview Schedule [DIS], Composite International Diagnostic Interview [CIDI], Mini-international Neuropsychological Interview [MINI], Clinician-Administered PTSD Scale [CAPS]) ranged from 2% to 32.5% (17 studies 18, 20, 23-25, 28, 30-32, 35, 37, 39, 41, 43-45, 58 ). The point prevalence of substantial PTSD/clinically important PTSD symptoms based on questionnaire thresholds ranged from 2.9% to 39.1% (15 studies 17, 19, 21, 22, 26, 27, 33, 38, 40, 42, 46, 5329, 34, 36 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The point prevalence of PTSD diagnosis ascertained by diagnostic interviews (e.g., Structured Clinical Interview [SCID], Diagnostic Interview Schedule [DIS], Composite International Diagnostic Interview [CIDI], Mini-international Neuropsychological Interview [MINI], Clinician-Administered PTSD Scale [CAPS]) ranged from 2% to 32.5% (17 studies 18, 20, 23-25, 28, 30-32, 35, 37, 39, 41, 43-45, 58 ). The point prevalence of substantial PTSD/clinically important PTSD symptoms based on questionnaire thresholds ranged from 2.9% to 39.1% (15 studies 17, 19, 21, 22, 26, 27, 33, 38, 40, 42, 46, 5329, 34, 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…The PTSD Checklist (PCL) (6 studies) 17, 22, 26, 38, 46, 53 and the Composite International Diagnostic Interview (CIDI) (6 studies) 20, 23, 25, 30, 37, 44 were the diagnostic tools most often used. The PCL is a screening measure while CIDI is a structured clinical diagnostic interview.…”
Section: Resultsmentioning
confidence: 99%
“…Its prevalence ranges from 6.6% to 21% across countries (Kessler and Bromet, 2013), rising to 18.3% in Qatar (Bener et al, 2015). Nearly 20% of patients with heart disease suffer from depression (Carney and Freedland, 2008;Elderon and Whooley, 2013;Thombs et al, 2006), while depression following myocardial infarction is associated with 2.25-to 2.38-fold risk of all-cause mortality and 2.59-to 2.71-fold risk of cardiac mortality (Meijer et al, 2011;van Melle et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…High prevalence of mental disorders in PHC settings was reported by some studies, for example, in Brazil (51.9%–64.3%) (Gonçalves et al, ) and in Kuwait (43%) (Ibanez et al, ). Many studies in different countries had reported much lower rates than these studies for example, in Qatar (20%) (Bener, Abou‐Saleh, Dafeeah, & Bhugra, ) and in Morocco (13.7%) (Oneib, Sabir, Abda, & Ouanass, ).…”
Section: Discussionmentioning
confidence: 93%